The Impact of Compact and Mixed Development on Land Value: A Case Study of Richmond, Virginia - I-Shian (Ivan) Suen (Urban Science, 2018)
Sustainable development entails various development patterns commonly associated with compact and mixed development that usually leads to reduced driving, more public transportation utilization, lower energy consumption, better walkability, and improved public health. To examine if the benefits of compact and mixed development are reflected in land value, this study sets forth to measure development compactness and land use mix and assesses the impacts of such patterns on land value. Impacts of accessibility to jobs, retail stores, and public transportation on land value are also investigated and compared to the impacts from development patterns. The study finds that: (1) accessibility has greater impacts than development pattern on land value; (2) compact development and mixed land use influence land value differently depending on the nature of existing land uses and land values; (3) accessibility to jobs and retail stores always contributes to the increase of land value; and (4) accessibility to public transportation helps but it does not influence land value in a consistent fashion. The results suggest that areas with higher residential property values, good proximity to the city center, less industrial land uses, and good access to jobs and retail stores have greater potential to realize an increase of land value resulted from compact and mixed development in Richmond, Virginia.